Perbandingan Kapasitas Paru-Paru Perokok dan Bukan Perokok pada Mahasiswa Olahraga Universitas - Harun, Harun; Kusumawati, Diah; Akbar, Muhammad Syifa Nurul (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2024)
Smoking is known to have adverse effects on lung health. Study shows that regular exercise is known to improve of the respiratory system health. Sports students are a group that has physical activity and exercise that meets the physical activity standards of 150 minutes of moderate intensity of aerobics physical activity per week, but many of the students are smoker. This study aims to determine the lung capacity of sports science study program students who smoke compared to students who do not smoke. This study was a cross-sectional study in which 32 male students of sports science departement Universitas Muhammadiyah Cirebon with an average age of 20 ± 1.28 years, an average body weight of 56.45 ± 8.26 kg, and a height of 165.58 ± 7.15 cm, were divided into two groups namely: smoking group (n = 16), and non-smoking group (n = 16). Subjects were asked to answer a questionnaire related to smoking habits and then the lung capacity of the research sample was measured using an SP70B spirometer (Contec Medical System Co., Ltd., China). Most of the smoking group (75%) consumed 1-5 cigarettes per day, with an average of 4.73 ± 3.15 years of smoking. The results of the measurement of force vital capacity (FVC) of the smoking group amounted to 3.31 ± 0.42 L with an average predicted %FVC is 74%. While the non-smoking group had an average FVC is 3.6 ± 0.6 L with an average %FVC is 80%. The results of the paired sample test found that there was a significant difference between the FVC of subjects who smoked and those who did not smoke with a significance value of 0.000 (P <0.05). The group of smoker students actively exercised had significantly lower lung capacity values than the group of students who actively exercised but non smoker. Non-smoker students had significantly better FVC (L) than smoker students (p=0.000). Thus, smoker students but actively exercised have lung capacity values that are at risk (FVC <80%).